Evening Chronotype Is Associated With Metabolic Disorders and Body Composition in Middle-Aged Adults - Yu, Ji Hee; Yun, Chang-Ho; Ahn, Jae Hee; Suh, Sooyeon; Cho, Hyun Joo; Lee, Seung Ku; Yoo, Hye Jin; Seo, Ji A; Kim, Sin Gon; Choi, Kyung Mook; Baik, Sei Hyun; Choi, Dong Seop; et al. (The journal of clinical endocrinology and metabolism, 2015)
Context:Chronotype is a trait determining individual circadian preference in behavioral and biological rhythm relative to external light-dark cycle. However, little is known about the relationship between chronotype and metabolic disorders.Objective:The aim of this study was to examine whether late chronotype is related to metabolic abnormalities and body composition in middle-aged adults, independent of sleep duration and lifestyle.Design and Participants:A total of 1620 participants aged 47–59 years were recruited from the Korean Genome and Epidemiology Study.Main Outcome Measures:Chronotype was assessed by the Morningness-Eveningness Questionnaire. Associations of chronotype with diabetes, metabolic syndrome, sarcopenia, and visceral obesity were analyzed. All participants underwent the oral glucose tolerance test, and body composition was measured with dual energy x-ray absorptiometry. Visceral obesity was designated as visceral fat area, measured by abdominal computed tomography, of >100 cm2.Results:Chronotype was classified as morning in 29.6% of subjects, evening in 5.9%, neither morning nor evening in 64.5%. Evening type, when compared with morning type, was significantly associated with diabetes (odds ratio [OR], 1.73; 95% confidence interval [CI], 1.01–2.95), metabolic syndrome (OR, 1.74; 95% CI, 1.05–2.87), and sarcopenia (OR, 3.16; 95% CI, 1.36–7.33) after adjusting for confounding factors. Gender differences in the associations were evident. In men, evening type was associated with diabetes (OR, 2.98; 95% CI, 1.39–6.39) and sarcopenia (OR, 3.89; 95% CI, 1.33–11.33). Only metabolic syndrome was associated with evening type in women (OR, 2.22; 95% CI, 1.11–4.43).Conclusions:At the population level, evening chronotype was independently associated with diabetes, metabolic syndrome, and sarcopenia. These results support the importance of circadian rhythms in metabolic regulation.